The impact of floral morphology on genetic differentiation in two closely related biennial plant species. Issue 5 (7th September 2018) - Mertens, Arne; Brys, Rein; Schouppe, Dorien; Jacquemyn, Hans
Abstract : In this work, we compare the genetic differentiation and structure of populations of two closely related Centaurium species that display a large variation in floral morphology across two geographic regions in Europe. The populations of both species show opposite patterns of genetic differentiation and structure, and the patterns are reversed between the two regions. For both species, we find a strong link between these patterns and the differences in floral morphology observed in the sampled populations. Abstract: The genetic diversity and structure of plant populations are determined by the interaction of three distinct processes: gene flow, genetic drift and natural selection. These processes are to some extent dependent on the mating system of plants, which in turn is largely determined by floral morphology and the level of herkogamy in particular. In this study, we used molecular markers to investigate the impact of floral morphology on genetic differentiation and structure in two closely related Centaurium species that display large variation in floral morphology across two distinct geographic regions in Europe (mainland Europe and the UK). Our results showed that genetic differences between regions and populations within regions were similar for both species, but that patterns of genetic structure largely depended on the observed variation in floral morphology. Populations of Centaurium erythraea showed higher genetic differentiation and clear isolation by distance (IBD) in mainland Europe, but limited IBD in the UK. Opposite patterns were found in Centaurium littorale, with higher genetic differentiation and significant IBD in populations sampled in the UK and lower genetic differentiation in Continental populations with no pattern of IBD. Overall, these results indicate that variation in floral morphology has a profound impact on structuring of genetic diversity, with populations displaying low levels of herkogamy showing the strongest patterns of genetic structuring and the reverse pattern in populations showing high levels of herkogamy.